2017
DOI: 10.1080/00952990.2017.1283695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drug-related cues on response inhibition through abstinence: A pilot study in male heroin abstainers

Abstract: Effect of drug-related cues on response inhibition remains at the early stage of abstinence; however, this effect may be reduced following a longer period of drug abstinence. Our findings highlight the importance of assessing and improving the ability of inhibiting drug-related cue reactivity during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
6
0
2
Order By: Relevance
“…For this, the research adopts the Two-Choice Oddball paradigm. In previous studies, this paradigm has been successfully used to examine BIC associated with substance use disorders (e.g., Su et al, 2017;Zhao, Liu, & Maes, 2017).…”
Section: Impulsivitymentioning
confidence: 99%
“…For this, the research adopts the Two-Choice Oddball paradigm. In previous studies, this paradigm has been successfully used to examine BIC associated with substance use disorders (e.g., Su et al, 2017;Zhao, Liu, & Maes, 2017).…”
Section: Impulsivitymentioning
confidence: 99%
“…Moreover, chronic opioid use and opioid dependence are associated with diminished cognitive control functions, including deficits in response inhibition [16][17][18][19], which can persist beyond cessation of and withdrawal from opioid use [20,21]. Opioid-dependent individuals exhibit attenuated inhibitory control-related fMRI BOLD signal in medial prefrontal circuitry, including the anterior cingulate cortex [22,23] and medial prefrontal cortex [24], and have worse behavioral performance compared with nonopioid-dependent persons across a broad range of task probes of response inhibition including the arrow task [25], the standard Go/NoGo task [22], and the affective Go/NoGo task [26].…”
Section: Opioid Use and Response Inhibitionmentioning
confidence: 99%
“…It is possible that deficits of inhibitions may be reduced with increased length of abstinence. In our recent study, we found that RT for drug-related deviants were shorted in longer-term heroin abstainers (16-24 months) compared to those having shorter period of abstinence (2-6 months) (Su et al, 2017). Longitudinal research should be implemented to clarify the cognition change induced by length of abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…Pictures used in our two-choice oddball paradigm were the same as those used in our previous studies (Su et al, 2017;Yang et al, 2015a) which included 20 neutral pictures (e.g. household objects, tools, neutral facial expressions) selected from International Affective Pictures System (IAPS) (Lang et al, 2005), and 20 heroin-related pictures consisting of the scenario of preparing or using heroin, drug or drug tool collected from freely available online sources.…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation